2017
DOI: 10.15740/has/au/12.2/262-265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of internet utilization on overall performance of agricultural research scholars of agriculture science inMPUAT, Udaipur (Rajasthan)

Abstract: SUMMARY :Internet has become a way of life for majority of higher education students all around the world. For most universities and college students, the internet is a functional tool, one that has greatly changed the way they interact with each other and with information as they go about their studies. Considering the importance of the internet utilization the present investigation "attitude and utilization pattern of internet among the research scholars of agriculture science in MPUAT, Udaipur (Rajasthan).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Physical activities, outdoor games and outings were avoided by respondents in the favour of binge-watching web series and online shows. The findings are in line with Choudhary et al, (2016); Emmanuel et al, (2019) & Pandey et al, (2020 who all revealed that consumption of online content has a number of negative effects on the respondents.…”
Section: Hypothesis Verificationsupporting
confidence: 89%
“…Physical activities, outdoor games and outings were avoided by respondents in the favour of binge-watching web series and online shows. The findings are in line with Choudhary et al, (2016); Emmanuel et al, (2019) & Pandey et al, (2020 who all revealed that consumption of online content has a number of negative effects on the respondents.…”
Section: Hypothesis Verificationsupporting
confidence: 89%